Insight into binding mechanisms of EGFR allosteric inhibitors using molecular dynamics simulations and free energy calculations. Issue 16 (2nd November 2019) - Wan, Shanhe; Yan, Ruohong; Jiang, Ying; Li, Zhonghuang; Zhang, Jiajie; Wu, Xiaoyun
Abstract: Lung cancer is the leading cause of cancer death, and epidermal growth factor receptor (EGFR) kinase domain mutations are a common cause of non-small-cell lung cancer (NSCLC), a major subtype of lung cancers. Patients harboring most of these mutations respond well to the EGFR inhibitors Gefitinib and Erlotinib initially, but soon develop resistance to them due to the emergence of the gatekeeper mutation T790M. The new-generation inhibitors such as AZD9291, HM61713, CO-1686 and WZ4002 can overcome T790M through covalent binding to Cys 797, but ultimately lose their efficacy upon the emergence of the C797S mutation that abolishes the covalent bonding. Allosteric inhibitors EAI001 and EAI045 are a new type of EGFR inhibitors that bind to EGFR away from the ATP-binding site and not relying on Cys 797. In this study, molecular dynamics simulations and free energy calculations were carried out on EAI001 and EAI045 in complex with EGFR, revealing the detailed inhibitory mechanism of EAI001 and EAI045 as EGFR allosteric inhibitor, which was expected to provide a basis for rational drug design of the EGFR allosteric inhibitors. Communicated by Ramaswamy H. Sarma